Offshore Utility Systems for FPSOs: A Techno-Environomic Assessment Considering the Uncertainty About the Natural Gas Price - Flórez-Orrego, Daniel; Albuquerque, Cyro; Da Silva, Julio A. M.; Freire, Ronaldo; De Oliveira Junior, Silvio (Frontiers in Chemical Engineering, 2022)
Due to restricted weight and space budget on floating production, storage and offloading units (FPSO), the offshore utility systems have been limited to low-efficiency energy technologies. Moreover, owing to time-varying energy demands of the FPSOs, the existing cogeneration systems incur oversizing issues and mostly operate at offdesign conditions during the lifespan. This situation increases the fuel consumption and accentuates the environmental impact of the offshore oil and gas sector. Accordingly, a power hub emerges as an interesting alternative to the conventional utility system, featuring more efficient and environmentally friendly energy solutions. Nevertheless, power hubs are not free from challenges, typically related to the incremental costs of additional power generation and transmission equipment and costly carbon abatement units. Thus, uncertain natural gas price, carbon taxation, and delay in entry of operation between productive platforms should be thoroughly considered in anticipation of the impact of volatile market prices and more stringent environmental regulations on the operational results of the assets. In this work, a comparative incremental assessment between the existing cogeneration system and four alternative power hub setups is performed to shed light on the potential benefits of adopting the centralized offshore power stations. Among those benefits are augmented revenues with gas exportation, optimal sizing and load dispatch process, and reduced number of idle power units, oftentimes required only for attending the peak demand that occurs in a short interval of the whole lifespan of the hub. As a result, it is found that by increasing the delay in entry of operation, the opportunity cost arisen from the money depreciation and the variation of the gas price over time substantially hampers the economic feasibility, showing a trade-off between the best thermodynamic performance, the lowest environmental burden, and the most profitable operating conditions.